Beginning VB 2008 - Gross, Christian (Apress, 2012)
The first computer programming book I read was titled Programming Windows 3.0 by Charles Petzold. This was around the time when Microsoft Windows 3.0 (circa 1992) once and for all showed the industry that Microsoft was a company with a future. Writing code for Windows back then was complicated by many things: lack of documentation, 16-bit architecture, and the necessity of buying a compiler separate from the software development kit (SDK). Charles’s book tied everything together and solved the problem of how to write a program for Windows. Now the problems are quite the opposite: we have too much documentation, we have 64-bit architectures, and everything including the kitchen sink is thrown into a development environment. Now we need to figure out what we actually need. We have too many options—too many ways to solve the same problem. What I am trying to do with this book is the same thing that Charles did for me when I first started out, and that was to help me figure out what I needed to write code. This book is about explaining the Visual Basic programming language in the context of solving problems. Visual Basic has become a sophisticated programming language that can achieve many goals, but you are left wondering what techniques to use when. This book is here to answer your questions.